2011
DOI: 10.1177/102490791101800404
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Survey on the Clinical Presentation of Ketamine Abusers in a Hong Kong Emergency Department

et al.

Abstract: Ketamine is one of the commonest abusing agents in Hong Kong. Our study aims to identify their clinical pattern of presentations to emergency departments. Method: This is a retrospective survey study. The studied group was ketamine abusers being referred to us from a source out of emergency department (ED). Control group was randomly selected from patients attending our ED. The electronic records of the ketamine abusers and the controls in the past 3 years (1st April 2004-31st March 2007) were reviewed and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…During data collection, a significant number of studies carried out in Hong Kong were found on ketamine misuse and its deleterious effects (65)(66)(67). The misuse of ketamine has been highly popular among Hong Kong teenagers since 2005.…”
Section: -Year-old Femalementioning
confidence: 99%
“…During data collection, a significant number of studies carried out in Hong Kong were found on ketamine misuse and its deleterious effects (65)(66)(67). The misuse of ketamine has been highly popular among Hong Kong teenagers since 2005.…”
Section: -Year-old Femalementioning
confidence: 99%